Effect of Recruitment, Compensation, and Job Satisfaction On Permanent Lecturer Retention at PTS Lldikti Region III Jakarta With Organizational Commitment as Mediato - Akhmad Tarigan, Budi; Hamidah, Hamidah; Nurjanah, Siti (Green Publisher Indonesia, 2022)
Recruitment, compensation, job satisfaction and organizational commitment are 4 (four) independent variables used to examine the retention of permanent lecturers at PTS LLDIKTI Region III Jakarta. This study uses the indirect effect of recruitment, compensation and job satisfaction on the retention of permanent lecturers at PTS LLDIKTI Region III Jakarta with organizational commitment as a mediator. This indirect effect can be determined through the direct influence of recruitment, compensation, job satisfaction and organizational commitment on the retention of permanent lecturers at PTS LLDIKTI Region III Jakarta and the direct influence of recruitment, compensation, job satisfaction on organizational commitment. The method used in this study is a quantitative method with a descriptive type of research that describes the phenomenon being studied through regression equations. The regression equation was determined after all research data were tested with validity, reliability, normality, multicollinearity and heteroscedasticity tests from 300 respondents who were samples of all permanent PTS lecturers with university legal entities located in LLDIKTI III d/h Kopertis Region III classified into cluster 4 (coaching), as many as 15 private universities with a total population of 1297 ( Kemendikbud RI, 2019). The simple regression equation is said to be significant and positive if tcount > t table. The multiple regression equation is significant and positive if Fcount > Ftable . The results showed that recruitment (X1), compensation (X2), job satisfaction (X3) and organizational commitment (X4) partially had a positive and significant effect on permanent lecturer retention (Y) because tcount > ttable ( 10,994 ; 6,243; 4,809 and 7,491 > 2,339 ). The effect in percent( %) is 28.9%; 11.6%; 7.2% and 15.8%. This effect is true because Fcount > Ftable (120.875; 38.976; 23.131 and 56.122 > 3,323). recruitment (X1), compensation (X2), and organizational job satisfaction (X3) partially have a positive and significant effect on permanent lecturer retention (Y). because tcount > ttable (18,405; 5,784 and 5,320 > 2338) The effect in percent (%) is 53.2%; 10.1% and 6.7%. This effect is true because Fcount > Ftable (338,747; 33,451 and 28,307 >3,323)